PENGARUH KEDALAMAN TERHADAP PERTUMBUHAN DAN PRODUKSI SERTA WARNA RUMPUT LAUT (Kappaphycus alvarezii) DI PERAIRAN PANTAI AMAL KOTA TARAKAN - Rukisah Rukisah; Burhanuddin Ihsan; Aswar Gunawan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
Seaweed is one of the fisheries commodities that are widely cultivated in Indonesia. Seaweed cultivation (Kappaphycus alvarezii) in the amal baru Coast of Tarakan City is carried out traditionally using the longline method so that the yield of seaweed (K. alvarezii) depends on natural conditions. One effort that can be done to optimize land use is vertical land use. The purpose of this study is to determine the effect of depth on the growth of seaweed production and color in the Amal Coast waters. This study uses a completely randomized design (CRD) with 3 treatments and 3 replications. This research was conducted for 21 days in the waters of the Amal Coast of Tarakan City. Data were analyzed using ANOVA and BNT follow-up tests. The test results showed that seaweed growth was significantly different between treatments 10 and 30 cm. The highest relative growth was in the 10 cm treatment of 109.22% and the lowest was 39.38%. The highest specific growth rate was in the 10 cm treatment of 3.56% / day and the lowest was 1.58% / day. The highest mean of seaweed production at 10 cm treatment was 36.407 g / m and the lowest was 13.130 g / m. The difference in growth is greatly influenced by the intensity of the light, the brightness of the waters, and the suspended solids. The color of the talus appears brighter at low depths compared to high depths. The intensity of light and nutrients affect the concentration of seaweed pigments.